THE EFFECTS OF ACTIVE LEARNING USING COOPERATIVE LEARNING (STAD) AMIDST THE COVID -19 PANDEMIC ON LEARNING ACHIEVEMENT AND SATISFACTION TOWARDS HEALTH EDUCATION LEARNING IN DRUG ISSUE OF GRADE 5 STUDENTS - Konglee, Jaranya; Kanjanasorn, Wayu (Journal for Developing the Social and Community, 2023)
The purpose of this research were 1) to study the effects of active learning using cooperative learning (STAD) on learning achievement amidst the Covid-19 pandemic 2) to study satisfaction. The sample of the study was the 43 in grade 5 students at Sanambin school, Khon Kaen Province which were chosen by Purposive sampling. This research is quasi-experimental research with one-group pretest- posttest design. Research instruments included 8 lesson plan, achievement test and satisfaction questionnaire. The data was analyzed by using statistics including mean, standard deviation and t-test dependent. The research findings were as follows: the post-test score of most students was higher than the pre-test score after using STAD cooperative technique in active learning class and was significantly higher than before at the .05. Moreover, the students had satisfaction showed there in highest level. Research conclusions: Students had higher academic achievement after they learned. They were satisfied with the learning management at the highest level. Students have practice and work in group with their friends, creative thinking, problem solving skill and good interactions with friends. They enjoy the class, have fun, and eager to learn more.